Cover Feature: Raffaello Nasini: An Eclectic Chemist Heralding the Interdisciplinary Essence of Inorganic Chemistry (Eur. J. Inorg. Chem. 5/2019). Issue 5 (23rd January 2019) - Macchioni, Alceo
Abstract : The Cover Feature shows the great Italian chemist Raffaello Nasini (1854–1931) surrounded by the Nasini Prize Winners who contributed to thisVirtual Issue and to the relatedWorkshop in Rome . More information can be found in theGuest Editorial by A. Macchioni .